Occurrence of benzotriazole UV stabilizers in coastal fishes - Montesdeoca-Esponda, Sarah; Torres-Padrón, María Esther; Novák, Martin; Krchová, Lucie; Sosa-Ferrera, Zoraida; Santana-Rodríguez, José Juan (Journal of environmental management, 2020)
Chemicals added in personal care products are of emerging concern because their fate and their effect on the environment is not completely known. Benzotriazole UV stabilizers (BUVSs) are compounds used in different cosmetic products, which may reach the marine environment through marine discharge from treated waters or directly from bathing areas. Once released into the aquatic ecosystem, BUVSs can be bioaccumulated by aquatic organisms. To identify the human exposure risk, it is important to have suitable analytical methods to determine the presence of BUVSs in these organisms. Because of the complexity of such a biological matrix, selective extraction and detection techniques are required to isolate and quantify these kinds of pollutants at trace levels. In the present work, we optimized a method based on microwave-assisted extraction combined with ultra-high performance liquid chromatography and mass spectrometry detection to determine six benzotriazole compounds in fish samples. The absolute extraction yields provided by the proposed method were higher than 40% for most compounds, with intra-day and inter-day relative standard deviations ranging from 0.27 to 6.06 and 1.12-21.3%, respectively. The limits of quantification were in the range of 1.13-9.66 ng g-1 (dry weight). The method was applied to the study of three species of fish (Boops boops, Sphyraena viridensis, Sphoeroides marmoratus) that were collected close to three marine outfalls of treated waters on the Gran Canaria Island (Spain) for two years. Four of the six studied compounds, UV-326, UV-328, UV-329 and UV-360, were found with concentrations ranging from 1.34 ng g-1 to 45.6 ng g-1 (dry weight).
Keywords: Fishes; tandemová hmotnostní spektrometrie; UV stabilizers; ryby; chemické látky znečišťující vodu; Marine outfalls; Ecosystem; Water Pollutants, Chemical; triazoly; Tandem Mass Spectrometry; Benzotriazole; Spain; Personal care products; ekosystém; Triazoles; zvířata; Španělsko; Sewage; Animals; Fish